Promoting Students' Higher Order Thinking Skills (HOTS) through Classroom English Debate in Critical Speaking Course at IAIN Bone Students - Maharajuddin, Musfirah; Zuhri DJ, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2023)
The analyzing, evaluating and creating skill that are drilled during debate practice have been shown to support students' critical thinking skill. It proves how debate inspires students to analyze a situation from their own point of view. This research, therefore, aimed to evaluate debate in promoting students’ higher order thinking skill, particularly among Students of English Education Program at IAIN Bone, South Sulawesi. The research adopted qualitative analysis in which observation and interview were used as data-gathering instruments. The findings showed that debate promoted students’ higher order thinking skill because in debating students are required to think critically according to aspects of Bloom's taxonomy, they were analyzing, evaluating and creating. However, there were several problems faced by some students during English debate classroom in critical speaking subject, namely trouble defining the motion, had a limited vocabulary, difficult to rebut the opponent's argument, the difficulty of expressing an argument and nervous when practicing debates because they have to think critically. Keywords: Debate, Higher Order Thinking Skill, Critical Speaking, Students’ Problem.